Environmental ethics at an intercultural garden (Scientific initiation in sustainability) - Gaspar, Sandra Ávila; Silva, Isabela de Souza Ramos; Bellizzi, Gabriela Miranda; Gomes, Nelson Bretas de Noronha; Bolognani , Fábio de Almeida; Branco, Morgana Teixeira Lima Castelo; Pyrrho , Alexandre dos Santos; Varricchio, Marcia Cristina Braga Nunes (Seven Editora, 2024)
This chapter represents the historical record of the stages of the third management of the intercultural didactic garden (medicinal and sensory) in a courtyard used by the Homeopathy Service, located in the 7th Infirmary of the Hospital Geral Santa Casa da Misericórdia in Rio de Janeiro/Brazil, whose elaboration was inter - transdisciplinary and intersectoral, voluntary and cooperative, with the purpose of cultural appreciation and intercultural and interethnic experience, as a way of promoting well-being and mental health through the preservation of intangible heritage, which is the knowledge of the people. The doctor and naturalist, who brought Homeopathic Medicine to Brazil at that time, cared for members and families of traditional ethnic communities and enslaved indigenous peoples or, when they no longer served, those left to fend for themselves. Therefore, from this stage completed in primary care, scientific initiations were carried out with the plant elements of the Benoit Jules Mure medicinal garden, ranging from in situ morphological knowledge to the pharmaceutical process using the Hahnemannian method of multiple bottles, to investigate circumscribed environmental issues . Scientific investigations were started with Calendula officinalis, Euphorbia tirucalli, Annona muricata. For the present stage described here, the germination of Cowpeas (Vigna unguiculata) was investigated, originating from Africa and used to this day by Quilombola Traditional Knowledge, selected based on a bibliographical review. Cowpea grown in this garden in cups with an high ultra-diluted and energized (HUD) 5DH Sulphur solution, as directed for organic garden cultivation in Rio de Janeiro, has broad potential for clinical scientific research in nutrition and the environment, also for phytoremediation. This study, with the use of streamlined solutions, thus contributed to expanding the perception regarding the positive and enriching role of cultural diversity and also biodiversity, helping both to reduce the risk of food shortages for those in urban situations in Rio de Janeiro, as well as in awareness of ethical behavior of care for everything that makes up the environment (Environmental Ethics) and Cultural Competence. DOI:https://doi.org/10.56238/sevened2023.001-019